2019
DOI: 10.15419/bmrat.v6i1.516
|View full text |Cite
|
Sign up to set email alerts
|

A type 2 diabetes mellitus patient was successfully treated by autologous bone marrow-derived stem cell transplantation: A case report

Abstract: Introduction: Type 2 diabetes mellitus (T2DM) iscurrently one of the most common diseases as a result of obesity and aging. Currently, T2DMis treated by various methods, such as insulin injection and glucose regulation agents. In this report, we report the case of a T2DM patient who was successfully treated by autologous bone marrow-derived stem cell transplantation. Methods: The patient was diagnosed with T2DM by standard methods for more than ten years. The patient agreed to be treated by the new appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…On the other hand, the infusion of BMSCs suppressed helper T-cell development, thus attenuating immune responses and inflammatory damage [147]. Type I and type II diabetes have been the targets of BMSCs therapy [148][149][150][151]. There are several completed and in processing clinical trials registered in the database of U.S National Library of Medicine that used BMSCs in phase I to phase III clinical trials.…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the infusion of BMSCs suppressed helper T-cell development, thus attenuating immune responses and inflammatory damage [147]. Type I and type II diabetes have been the targets of BMSCs therapy [148][149][150][151]. There are several completed and in processing clinical trials registered in the database of U.S National Library of Medicine that used BMSCs in phase I to phase III clinical trials.…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
“…There are several completed and in processing clinical trials registered in the database of U.S National Library of Medicine that used BMSCs in phase I to phase III clinical trials. After nine months of BMSCs intravenously transfusion, diabetic patients are free from insulin injections without any side effects [151]. In addition, a randomized trial in 21 patients who underwent BMSCs infusion of a superior pancreaticoduodenal artery or splenic artery significantly reduced the insulin requirement dose, but did not show the improvement of insulin sensitivity [150].…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
“…A study on the viability of engineered pancreatic islets in hypoxic environments, when co-cultured with Wharton’s jelly MSCs, showed higher viability, higher vascularisation and increased anti-inflammatory cytokines compared to negative controls ( 129 ). Studies reported that insulin requirement and haemoglobin A1c (HbA1c) levels had decreased following transplantation of autologous BM-MSCs in T2DM patients ( 22 , 130 ). However, the effects of SCT were short-lived suggesting this treatment is more efficacious in patients with less than 10 years of T2DM and body mass index of less than 23 ( 131 ).…”
Section: Current Updates In Stem Cell Therapy In Various Diseasesmentioning
confidence: 99%
“…Since then, many milestones have been achieved in the field of SCT ( Figure 2 ). SCT has been applied in various intractable diseases such as haematological diseases ( 17 , 18 ), neurological diseases ( 19 , 20 ), diabetes mellitus ( 21 , 22 ), retinal degenerative disorders ( 23 , 24 ) and COVID-19 infections ( 25 , 26 ). With positive therapeutic outcomes of stem cell research, various stem cell techniques have been innovated such as stem cell isolation methods and in vitro cell culture protocols ( 7 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a major disease that is on the rise worldwide 1,2 . In this disease, insulin resistance or defects in insulin secretion lead to a metabolic disorder caused by hyperglycemia 2,3 . The disease is divided into two subgroups: type 1 diabetes and type 2 diabetes 4 .…”
Section: Introductionmentioning
confidence: 99%